23.1k views
5 votes
The expression _______ is not equivalent to (1 − sin2(x)) tan(-x).

a. (1 - cos^2(x)) cot(-x)
b. (cos^2(x) - 1) cot(x)
c. (sin^(x) - 1) tan(x)
d. (cos^2(x) - 1) cot(-x)

2 Answers

4 votes

Answer:

d. (cos^2(x) - 1) cot(-x)

Explanation:

User Lee Huang
by
5.7k points
4 votes

Answer:

D

Explanation:

First simplify given expression:


(1-\sin ^2x)\cdot \tan (-x)=\cos^2x\cdot (-\tan x)=-\cos^2x\cdot (\sin x)/(\cos x)=-\cos x\sin x.

Now consider all options:

A. True


(1-\cos^2 x)\cdot \cot (-x)=\sin^2 x\cdot (-\cot x)=-\sin^2 x\cdot (\cos x)/(\sin x)=-\sin x\cos x=-\cos x\sin x.

B. True


(\cos^2 x-1)\cdot \cot x=-\sin^2 x\cdot \cot x=-\sin^2 x\cdot (\cos x)/(\sin x)=-\sin x\cos x=-\cos x\sin x.

C. True


(\sin ^2x-1)\cdot \tan x=-\cos^2x\cdot \tan x=-\cos^2x\cdot (\sin x)/(\cos x)=-\cos x\sin x.

D. False


(\cos^2 x-1)\cdot \cot (-x)=(-\sin^2 x)\cdot (-\cot x)=\sin^2 x\cdot (\cos x)/(\sin x)=\sin x\cos x=\cos x\sin x.

User Vidish Purohit
by
6.2k points